Self-Objectificationas Representation of Postfeminist Women Empowerment in Fifth Harmony’s Music Videos. - Muslim, Bukhori (Jurnal Bahasa, Sastra, dan Studi Amerika, 2021)
This research attempts to describe the image of women empowerment in the era of postfeminism that is represented by Fifth Harmony’s self-objectification image in their four music videos; Work from Home, Boss, Worth It and That’s My Girl. This research is descriptive qualitative. The method employed consists of watching, classifying and analyzing the data that are collected by selecting the scenes, lyrics and other elements of music video representing the image of self-objectification and postfeminism.From the analysis, Fifth Harmony in their music videos use their self-objectification image to portray the values of women empowerment in post-feminism era. The music videos are portraying the issues of domesticity (femininity and sexuality) as women’s choice and source of power, confident and successful independent women as a symbol of Girl Power and sisterhood as source of women’s power in the era of postfeminism.